A behavioral approach to strategy—what's the alternative? - Levinthal, Daniel A. (Strategic Management Journal, 2011)
Abstract The strategy field has generally been viewed as somewhat fragmented with the primary ‘fault line’ stemming from the divide between economic and behavioral approaches. It is argued here that this is a false divide as any but the most trivial problems require a behavioral act of representation prior to invoking a deductive, ‘rational’ approach. In this sense, all approaches are behavioral. Once we recognize rationality as a process, then the pragmatic question becomes which among the imperfect mechanisms to guide choice and behavior may be more or less preferred. Such a viewpoint not only serves to help span the chasm of behavioral and economic approaches, but it may also connect the applied normative frameworks and approaches within the field to more theoretically grounded approaches. Copyright © 2011 John Wiley & Sons, Ltd.